Implementasi Pola Asuh Al-Ummu Madrasatul Ula dalam Membentuk Karakter Anak Kiai - Selawati Selawati; Siti Wahyuni (LPTK IAIN Kediri, 2023)
This study aims to determine how Al-Ummu Madrasatul ula parenting is implemented from the perspective of dhurriyyah parenting at the Lirboyo Islamic Boarding School HM Al-Mahrusiyah in shaping the character of the kyai's children. Al-ummu Madrasatul Ula parenting is one form of education a mother gives her child. This study uses Baumirnd's theoretical framework regarding parenting which is categorized into three types, namely: authoritarian parenting, democratic parenting, and permissive parenting. From the description above, the research problems can be formulated as follows: (1) how is the implementation of dhurriyyah parenting at the Lirboyo Islamic Boarding School HM Al Mahrusiyah as al-ummu madrasatul ula in shaping the character of the kyai's children? (2) what are the implications of the dhurriyyah upbringing of the Lirboyo Islamic Boarding School HM Al-Mahrusiyah in shaping the character of the kyai's children? So from the formulation of the problem above, the research objectives can be taken as follows: (1) describing the implementation of the dhurriyyah parenting pattern of the Lirboyo Islamic Boarding School HM Al Mahrusiyah as al-ummu madrasatul ula in shaping the character of the kyai's children (2) explaining the implications of dhurriyyah parenting at the Lirboyo Islamic Boarding School HM Al-Mahrusiyah in shaping the character of the kyai's children. This research uses qualitative research with a case study approach to implementing al-ummu madrasatul ula parenting in shaping the role model of the kyai's children. Data collection techniques used direct observation of the residence of the in-depth interviews with several dhurriyyah informants, abdi ndalem, chairman of the Lirboyo Islamic Boarding School HM Al-Mahrusiyah, and the editor-in-chief of the Mahrusy press, and using documentation techniques. The data analysis process uses the method used by Miles and Huberman, which is carried out continuously until it is complete with data reduction, data display, and conclusion. Conclusion drawing or verification. The results of the study, namely: (1) the implementation of dhurriyyah parenting at the Lirboyo Islamic Boarding School HM Al-Mahrusiyah as al-ummu madrasatul ula in shaping the character of kyai children by using a combination of parenting patterns such as the following: a) authoritarian parenting, b) democratic parenting, and c) permissive parenting. 2) the implications of dhurriyyah make the characters of his sons and daughters accustomed to asking permission, apologizing, asking for help, and being sociable.